THE SPIRIT OF CONFUCIANISM IN THE DEVELOPMENT OF A HUMANIST ACCOUNTING PROFESSION - Wika Harisa Putri; Nurdin Nurdin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Confucianism is a doctrine that invites us always to be agile in dealing with actual situations and conditions. Moreover, with its teachings and values such as self-civilization, moral example and prioritizing virtue ethics, these Confucian values are relevant to inspire and motivate accounting professionals to carry out their professional duties. The value of humanism contained in Confucianism aims to bring inner and outer happiness so that humans, as the centre of happiness, must be able to produce a better quality of life. The golden rule of Confucianism, "Do not do unto others what you would not want others to do unto you, " can inspire the accounting profession to act and think fairly to solve their professional job.